THE USE OF SPECIAL METHODOLOGIES FOR THE CORRECTION OF CHILDREN WITH VISUAL IMPAIRMENT AND ITS IMPORTANCE - Rimbayeva Ozoda Bazarbayevna (International Journal of Economic Integration and Regional Competitiveness, 2024)
the development of individuals with visual impairment is fundamentally different from other healthy individuals, and this defect does not remain without its own impact on their development, lifestyle. This article will talk about the features of speech of persons with visual impairments and special techniques used in the correction of children with visual impairments.